1993
DOI: 10.1161/01.res.72.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysolipids and oxidatively modified low density lipoprotein on endothelium-dependent relaxation of rabbit aorta.

Abstract: Exposure of isolated arteries to oxidatively modified low density lipoprotein (LDL) has been reported to suppress endothelium-dependent relaxation (EDR). To determine whether lipid degradation products in oxidized LDL contribute to impaired relaxation, we have tested the responsiveness of isolated rabbit aortas to endothelium-dependent relaxants (acetylcholine, ATP, and calcium ionophore A23187) and nitroglycerin before and after 2-hour incubations with selected lipids and LDL preparations. Concentrations (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…9 Matsuda and coworkers 31 reported that this effect was reversed by HDL and that HDL also reversed inhibition of endothelialderived relaxation caused by addition of LPC alone. Moreover, they demonstrated that HDL inhibited incorporation of radiolabelled LPC into cultured endothelial cells and stimulated the efflux of LPC from the cells into the culture medium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 Matsuda and coworkers 31 reported that this effect was reversed by HDL and that HDL also reversed inhibition of endothelialderived relaxation caused by addition of LPC alone. Moreover, they demonstrated that HDL inhibited incorporation of radiolabelled LPC into cultured endothelial cells and stimulated the efflux of LPC from the cells into the culture medium.…”
Section: Discussionmentioning
confidence: 97%
“…5 Although less reactive than PAF, LPC markedly affects the function of inflammatory cells. 8 It also inhibits endothelial-dependent arterial relaxation 9 ; activates endothelial expression of vascular cell adhesion molecule-1 and intercellular adhesion molecule-1, 10 as well as endothelial release of platelet-derived growth factor and heparin-binding epidermal growth factor-like protein 11 ; stimulates the macrophage production of tumor necrosis factor-␣ 12 ; and promotes SMC proliferation. 13 These findings suggest that PAF and LPC accumulation during intimal oxidation of LDL may be involved in activation of the inflammatory process and SMC proliferation associated with the formation of fibrous and complicated atherosclerotic plaque.…”
mentioning
confidence: 99%
“…Inhibition of relaxation to A23187 by Ž oxidised LDL has been demonstrated in rabbit aorta Jacobs . et al, 1990;Mangin et al, 1993although Tanner et al Ž . 1991 found no significant effect in porcine coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase B (PhlpB) (or Lysolecithinase B) catalyzes the hydrolysis of lysolecithins to glycerophosphorilcholine and FA. Oxidized LDL lipoproteins, that play a pivotal role in the development of atherosclerosis, contain lysolecithins that also cause the alteration of the vasal tone by impairing the endothelium-dependent relaxation [12]. On the other hand, lysolecithin concentration may significantly increase in the atherosclerotic arterial walls, and its cytotoxicity at high concentration may contribute to the cell death observed in the atheromatous lesions.…”
Section: Discussionmentioning
confidence: 99%